2021
DOI: 10.1007/s10984-021-09379-6
|View full text |Cite
|
Sign up to set email alerts
|

Student enrollment decisions and academic success: evaluating the impact of classroom space design

Abstract: Instruction based on active learning is being promoted in higher education by the creation of new collaborative teaching and learning spaces, but capacity does not yet exist for all courses to be held in these new spaces. In this study, we examined how students choose between sections of the same course, with the same materials and techniques used by the same instructor, delivered in a collaborative teaching and learning space compared with a lecture-theater space. We also measured how the factors used in enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…We also highlight these observed changes are not associated with substantive differences in practical instructional behavior from the professor, as confirmed by previous observations we conducted (Ralph et al, 2022). In many enrollment decisions students encounter between active learning settings and passive learning settings there will be instructional differences as well – either intentionally or unintentionally.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We also highlight these observed changes are not associated with substantive differences in practical instructional behavior from the professor, as confirmed by previous observations we conducted (Ralph et al, 2022). In many enrollment decisions students encounter between active learning settings and passive learning settings there will be instructional differences as well – either intentionally or unintentionally.…”
Section: Discussionsupporting
confidence: 90%
“…For the CLASS-C, Adams et al (2008) originally reported the instrument measured as many as nine constructs related to learning chemistry. However, subsequent revisions of the instrument have reduced the scales to measuring three constructs that can be measured together in a single administration with acceptable validity and reliability (Douglas et al, 2014; Heredia and Lewis, 2012; Ralph et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies have shown that students perform better academically when learning via their preferred method (4,5). Furthermore, a recent study demonstrated that honor students and women are more likely to choose collaborative learning environments (31), which may be because of a preference for active learning methods. Although selection bias could have been a factor influencing learning outcomes, the findings from the introductory course demonstrate that the student populations (those who did and did not do the activity) in the introductory immunology course were comparable (Fig.…”
Section: Discussionmentioning
confidence: 99%